2010
DOI: 10.1210/en.2009-1227
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Zebrafish Reveal Unusual Cellular Expression Patterns of Gonadotropin Receptor Messenger Ribonucleic Acids in the Testis and Unexpected Functional Differentiation of the Gonadotropins

Abstract: This study aimed to improve, using the zebrafish model, our understanding of the distinct roles of pituitary gonadotropins FSH and LH in regulating testis functions in teleost fish. We report, for the first time in a vertebrate species, that zebrafish Leydig cells as well as Sertoli cells express the mRNAs for both gonadotropin receptors (fshr and lhcgr). Although Leydig cell fshr expression has been reported in other piscine species and may be a common feature of teleost fish, Sertoli cell lhcgr expression ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
128
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 80 publications
(109 reference statements)
10
128
0
1
Order By: Relevance
“…Irrespective of the mechanism(s) involved, our This has been shown in Japanese eel [31], African catfish [17], and zebrafish [18]. Indeed, Fsh was 23 more potent as steroidogenic hormone than Lh in both catfish [60] and zebrafish [18]. Moreover, Fsh…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Irrespective of the mechanism(s) involved, our This has been shown in Japanese eel [31], African catfish [17], and zebrafish [18]. Indeed, Fsh was 23 more potent as steroidogenic hormone than Lh in both catfish [60] and zebrafish [18]. Moreover, Fsh…”
mentioning
confidence: 69%
“…but not Lh was able to up-regulate the expression of steroidogenesis related genes in juvenile eel 25 [24] and in adult zebrafish testis [18]. Therefore, we propose that Fsh, rather than Lh, mediated the 26 up-regulation of the steroidogenic capacity of the testis remaining after ULG.…”
mentioning
confidence: 77%
“…It can be hypothesized that only in Leydig cells there is an appropriate cellular context for transcriptional inhibition by E 2 . Another hypothesis is that E 2 exerts a negative feedback on the brain/pituitary system, resulting in a reduced gonadotropin release and consequently a fading stimulation of cyp17a1 gene expression and Cyp17a1 synthesis in Leydig cells that, in contrast to germ cells, express receptors for both Fsh and Lh in fish (Garcia-Lopez et al 2010).…”
Section: Figurementioning
confidence: 99%
“…These different responses could be based on the developmental stage of the gonadal tissue, and therefore in the presence of the corresponding GTH receptors. In zebrafish it has been suggested that the higher levels of fshr expression could explain the higher potency of Fsh [57]. In our study, the cultured testes were in late spermatogenesis, and there is no difference in GTH receptor expression at that gonadal stage [59].…”
Section: Discussionsupporting
confidence: 44%
“…In coho salmon, Lh was progressively more potent than Fsh in stimulating 11-KT production as spermatogenesis progressed through stage IV [56]. However, in zebrafish and channel catfish, recombinant Fsh was more effective in stimulating androgen release than Lh [49,57]; and in African catfish testis, the amount of Fsh needed to obtain a significant steroid release was lower than that of Lh [58]. These different responses could be based on the developmental stage of the gonadal tissue, and therefore in the presence of the corresponding GTH receptors.…”
Section: Discussionmentioning
confidence: 99%